Numerical Study of the Influence of the Geometrical Irregularities on Bodies of Revolution at High Angles of Attack - José Jiménez-Varona; Gabriel Liaño (Computation, 2022)
The flow at high angles of attack over axisymmetric configurations is not symmetric. The mechanism that triggers the asymmetry may be a combination of a global or hydrodynamic instability (temporal instability) combined with a convective instability (spatial instability) due to microscopic irregularities of the configuration. Poor repeatability of experiments and large differences in the global forces have been obtained with very small changes of the nose tip. In order to study theoretically this phenomenon, numerical simulations have been conducted for an ogive-cylinder configuration at subsonic flow and high angle of attack. For the numerical prediction of the flow about a missile type configuration, an assessment of the effect of structured and unstructured meshes is very important. How the body surface is modelled is very relevant; especially the tip zone of the body. Either configuration resembles a smooth or a rough model. The effect of the turbulence models is also decisive. The analysis has led to the conclusion that only Reynolds stress turbulence models (RSM) combined with Scale Adaptive Simulation (SAS), are the appropriate theoretical tools for the characterization of this flow. The geometrical similarity is very important. There is a roll or orientation angle effect for the unstructured grid, while the structured grid presents a bi-stable solution, one mirror of each other.